PENGEMBANGAN PERLUASAN AREAL TANAM DALAM PENINGKATAN PRODUKSI KACANG TANAH (Arachis hypogaea L) DI KABUPATEN PATI - Sutrisno Sutrisno (Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kabupaten Pati, 2019)
ENGLISHPeanuts are legumes commodity important after soybeans. Objectives of the research are to identify internal environment , external and formulate development strategies planting expansion in increased peanuts production in Pati regency. The research method uses descriptive with primary data source derived from observation and in-depth interviews with informants department of agriculture crops and livestock, farmer instructor, Agricultural Extension, community leaders, peanut farmers and stakeholders in 8 subdistrict centers of peanut plants, while the secondary data obtained from relevant documents. Data analysis using descriptive and SWOT . The results showed, among others : (1) land optimization with the support of the implementation of PAT peanut program, (2) improving institutional effectiveness and institutional farmer extension. INDONESIAKacang tanah merupakan komoditas kacang-kacangan yang penting setelah kedelai. Penelitian ini bertujuan untuk mengindentifikasi lingkungan internal, eksternal dan merumuskan strategi pengembangan perluasan tanam dalam peningkatan produksi kacang tanah di Kabupaten Pati. Metode penelitian menggunakan deskriptif dengan sumber data primer berasal dari observasi dan wawancara mendalam dengan narasumber Dispertannak, Mantri tani, Penyuluh Pertanian, Tokoh masyarakat, petani kacang tanah dan Stakeholders di 8 Kecamatan sentra tanaman kacang tanah, adapun data sekendair diperoleh dari dikumen yang relevan. Analisis data menggunakan deskriptif dan SWOT analisis. Hasil penelitian menunjukkan antara lain: optimasi lahan dengan dukungan pelaksanaan program PAT kacang tanah dan meningkatkan efektivitas kelembagaan penyuluhan dan kelembagaan petani.